De-Medicalizing Misery
XIV, 305 p.
Keywords: Psychiatry and psychology have constructed a mental health system that does no justice to the problems it claims to understand and creates multiple problems for its users. Yet the myth of biologically-based mental illness defines our present. The book rethinks madness and distress reclaiming them as human, not medical, experiences.